Productivity of duckweed (Lemna minor) as alternative forage feed for livestock in different light intensities - Uti Nopriani; PDMH Karti; Iwan Prihantoro (Indonesian Center for Animal Research and Development (ICARD), 2014)
Duckweed (Lemna minor) is a small aquatic plant that grow and float in water and spread extensively. Lemna minor is potential as a source of high quality forage. This study aimed to determine optimal light intensity on Lemna minor to generate maximum productivity. Parameters observed were physical-biological and chemical characteristics of the media (pH value, temperature, cover area, decreased of media volume, BOD, COD, nitrate, nitrite and phosphate), plant growth acceleration (number of shoots, leaf diameter and chlorophyll-a), biomass production, doubling time of cover area and the number of daughters. This study was done based on a completely randomized design with 4 levels of shading. While treatment was: without shading, shading 30%, shading 50% and shading 70% using paranet shade. Each treatment consisted of 4 replications. Result showed that the productivity of Lemna minor included the number of daughters, chlorophyll-a, biomass production, cover area, absorbed phosphate and doubling time the number of daughters reached the highest level without shading treatment (1007,21-2813,57 lux). The decrease of intensity of light, the increase the diameter of leaf. Decrease of media volume was positively correlated to size of cover area. Biomass production influenced by a wide doubling time of cover area and number of daughters.